2010
DOI: 10.1007/s10803-010-1098-4
|View full text |Cite
|
Sign up to set email alerts
|

Face Processing in Children with Autism Spectrum Disorder: Independent or Interactive Processing of Facial Identity and Facial Expression?

Abstract: The current study investigated if deficits in processing emotional expression affect facial identity processing and vice versa in children with autism spectrum disorder. Children with autism and IQ and age matched typically developing children classified faces either by emotional expression, thereby ignoring facial identity or by facial identity disregarding emotional expression. Typically developing children processed facial identity independently from facial expressions but processed facial expressions in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 51 publications
0
21
1
Order By: Relevance
“…The current findings are similar in that there were significant differences between the groups for the face memory component but only modestly for the face identity task without a delay. Additionally, children with ASD were no different from TD on their ability to distinguish different facial expressions, which has also been an inconsistent finding in the literature [8,28,29] (for a review see [63]). It is possible that the measures of affect recognition used across these studies may not be sensitive enough to detect the subtle impairment seen in some individuals with ASD [64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current findings are similar in that there were significant differences between the groups for the face memory component but only modestly for the face identity task without a delay. Additionally, children with ASD were no different from TD on their ability to distinguish different facial expressions, which has also been an inconsistent finding in the literature [8,28,29] (for a review see [63]). It is possible that the measures of affect recognition used across these studies may not be sensitive enough to detect the subtle impairment seen in some individuals with ASD [64].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Kuusikko and colleagues [28] found that children with ASD had poorer performance on an emotion recognition test compared to TD children and often misconstrued more ambiguous stimuli as showing negative emotions. Krebs and colleagues [29] also showed differences in facial and emotion processing which the authors speculate may be due to children with ASD processing face identity and affect separately, whereas TD children process them simultaneously. In a study of facial scanning, individuals with ASD showed impaired performance in emotion recognition primarily for fear [30].…”
Section: Introductionmentioning
confidence: 99%
“…Crucially, adults are able to switch strategies between face processing tasks so that they can ignore changes in expression when judging identity, and ignore changes in identity when judging expression. Young children appear to be less flexible, so that while they may be able to process face identity independently from facial expressions, changes in identity interferes with their ability to judge emotion from facial expressions (Krebs et al, 2011). The ability to use different processing strategies for the two tasks may appear rather abruptly, if it depends on the achievement of some attentional threshold (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Next, the BFRT and the FGT-D do not measure face processing methods (i.e., feature vs. a configural strategy). Not understanding face processing strategies has confounded studies with results that come about from participants using alternative strategies that often produce the same scores on face processing measures as produced by typical processing methods (Duchaine & Weidenfield, 2003;Hefter, Manoach, & Barton, 2005;Krebs et al, 2011). A further limitation was that there was no comparison group of individuals with intellectual disability.…”
Section: Discussionmentioning
confidence: 99%